Faktor individu dan lingkungan dengan citra tubuh pada santri putri di pondok pesantren - Labiqotul Fatiyasani; Ika Ratna Palupi; Tjaronosari Tjaronosari (Jurnal Gizi Klinik Indonesia, 2018)
Background: Perception and judgment against one’s own body is called body image. Limited studies have been performed on body image of the population living in boarding schools who has relatively homogeneous environmental characteristics and restricted access towards communication media.Objective: To determine the correlation between individual factors and environmental factors with body image of female students at religious boarding school.Methods: A cross-sectional study was conducted in 142 female students aged 15-19 years old in Islamic Centre Bin Baz (ICBB) boarding school Bantul. Individual factors included nutritional status, nutritional knowledge, and self-esteem, respectively measured by using BMI/age that interpreted using manual from Ministry of Health 2010, multiple choice questionnaire, and Rosenberg Self-Esteem Scale (RSE). Environmental factors encompassed culture, social economic status, and social support, respectively measured by using check lists of parent’s ethnics, social economic status questionnaire, Social Support Questionnaire Number (SSQN) and Social Support Questionnaire Satisfaction (SSQS). Body image was measured using CDRS (The Contour Drawing Rating Scale) form. All variables were tested using chi square test and logistic regression.Results: Individual factors that had significant correlations with body image were nutritional status (p<0.05; RP=1.3; 95%CI=2.68-2.83) and self-esteem (p<0.05; OR=21.3; 95%CI=3.97-114.3). Meanwhile, for environmental factors, they were social economic status (p<0.05) and social support satisfaction (p<0.05; 95%CI=0.02-0.95).Conclusion: Individual and environmental factors have correlation with body image of female students at religious boarding school.